Aspectos genéticos e qualidade fisiológica de sementes crioulas de Phaseolus Lunatus l.. - Nascimento, Maria das Graças Rodrigues do (2020)
Lima bean (Phaseolus lunatus L.) is among the most produced beans worldwide, providing vegetable protein for human and animal feed and serving as green manure or crop cover for soil protection. This study quantifies the genetic diversity in bean seeds native from Brazil and evaluates these seeds' physical, physiological, and sanitary quality. The seeds were purchased from family farmers in the states of Paraíba and Pernambuco. Cytogenetic analyses were performed on 19 landraces using the fluorochrome staining method CMA and DAPI. Uni and multivariate analyzes estimated the genetic diversity from 29 landrace seeds, which were quantitative and qualitatively characterized. Physiological quality analyses comprised the water content, weight of a thousand seeds, evaluation of germination and vigor (first germination count, germination speed index, length and dry mass of seedlings, tetrazolium test, electrical conductivity), and chemical composition. For the simulation of saline stress, sodium chloride (NaCl) was used in the concentrations of 0.0 (control), 2.0, 4.0, 6.0, 8.0, and 10.0 dS m-1 . Each treatment underwent germination tests. Two hundred seeds were used divided into four repetitions of 50. The first count and germination speed index were recorded during the germination test. The length and dry mass of roots and aerial part of seedlings were measured at the end of germination tests. Normal seedlings (with primary root and hypocotyl) in a row were placed in drying ovens to estimate dry mass weight. The sanitary and physiological quality analyses used seeds of six of P. lunatus landraces (Branca, Cancão, Cavalinha, Manteiguinha, Orelha de Vó, and Rainha). We evaluated the following variables: fungal occurrence, germination, first count, and germination speed index. The cytogenetic analysis showed that all landraces have 2n = 22 chromosomes. Karyotypes have an average size between 2.45 and 5.85 µm are relatively symmetrical and predominantly metacentric. The analysis of variance showed genetic variability among the landraces of P. lunatus for all evaluated characteristics. Landraces indicated for selection are Branca, Coquinho Moita Vermelha, Miúda, Manteiga, Raio de Sol, Orelha de Vó. The positive correlation between the germination tests and the vigor of the P. lunatus is important landraces seeds, as this can identify the existence of interrelationship between these tests. The landraces differ in the physiological quality and vigor of seeds. Landraces also differed when germinated under saline stress up to 10 dS m-1 . Fungal infections varied both between and within landraces. Percentage of germination, first count, and the germination speed index were higher than 90% for the seeds of five landraces, except for Cavalinha. The fungi genera found in the seeds were: Alternaria sp., Aspergillus sp., Basiodiplodia sp., Cladosporium sp., Fusarium sp., Penicillium sp., Rhizopus sp., Rhizoctonia sp., and Trichoderma sp; Penicillium sp. it is a fungus with higher incidence among the landraces varieties of P. lunatus.